Human Cytomegalovirus IE2 86 kDa Protein Induces STING Degradation and Inhibits cGAMP-Mediated IFN-β Induction - Kim, Jung-Eun; Kim, Young-Eui; Stinski, Mark F.; Ahn, Jin-Hyun; Song, Yoon-Jae (Frontiers in Microbiology, 2017)
Stimulator of interferon genes (STING) is a critical signaling molecule in the innate immune response against DNA viruses by either directly sensing intracellular DNA or functioning as an adaptor molecule to activate the type I interferon (IFN) signaling pathway. We determined the functional interaction between STING and human cytomegalovirus (HCMV). A cDNA library containing 133 HCMV ORFs was screened to identify viral genes that inhibit STING-induced IFN-β promoter activation. Among the screened ORFs, UL122, which encodes the immediate-early 2 86kDa (IE86) protein, strongly abolished STING-induced IFN-β promoter activation. Interestingly, IE86 protein facilitated the proteasome-dependent degradation of STING and inhibited 2’3’-cGAMP-mediated induction of IFNB1 and CXCL10. Taken together, this study demonstrates the existence of a post-translational regulation of STING by HCMV IE86 protein.